ITPA, TPMT, and NUDT15 Genetic Polymorphisms Predict 6-Mercaptopurine Toxicity in Middle Eastern Children With Acute Lymphoblastic Leukemia - Moradveisi, Borhan; Muwakkit, Samar; Zamani, Fatemeh; Ghaderi, Ebrahim; Mohammadi, Ebrahim; Zgheib, Nathalie K. (Frontiers in Pharmacology, 2019)
Background Acute Lymphoblastic Leukemia (ALL) is the most common cancer seen in children worldwide and in the Middle East. Although there have been major advances in treatment approaches for childhood ALL, serious toxicities do occur but with significant inter-individual variability. The aim of this study is to measure the frequency of polymorphisms in candidate genes involved in 6-Mercaptopurine (6-MP) disposition in a combined cohort of Middle Eastern Children with ALL, and evaluate whether these polymorphisms predict 6-MP intolerance and toxicity during ALL maintenance therapy. Methods The study includes children treated for ALL on two treatment protocols from two cohorts; one from Lebanon (N=136) and another from Kurdistan province of Iran (N=74). Genotyping for the following six candidate genetic polymorphisms: ITPA 94C>A (rs1127354) and IVS2+21A>C (rs7270101), TPMT*2 238G>C (rs1800462), TPMT*3B 460G>A (rs1800460) and *3C 719A>G (rs1142345), and NUDT15 415C>T (rs116855232) was performed and analyzed in association with 6-MP dose intensity and toxicity. Results As expected, TPMT and NUDT15 variants were uncommon. As for ITPA, both polymorphisms were more common in the Lebanese as compared to the Kurdish cohort with a minor allele frequency of 0.05 for 94C>A and 0.14 for IVS2+21A>C in the Lebanese only (N=121), and of 0.01 for either ITPA polymorphism in Kurds. The most significant toxic effects were depicted with the NUDT15 polymorphism with a median 6-MP dose intensity of 33.33%, followed by 46.65% for TPMT*3A polymorphism, followed by 65.33% for two ITPA risk allele carriers and 74% for one ITPA risk allele carriers, in comparison to a median of 100% for the homozygous wild type in the combined cohort (P<0.001). In addition, the onset of febrile neutropenia was significantly higher in variant allele carriers in the combined cohorts. Conclusions These data confirm the predictive role of TPMT, NUDT15, and ITPA in 6-MP intolerance in Middle Eastern children with ALL. Given the relatively high frequency of ITPA variants in our study and their significant association with 6-MP dose intensity, we recommend that physicians consider genotyping for ITPA variants in conjunction with TPMT and NUDT15 prior to 6-MP therapy in these children.